Utilizing English Tiktok as a Media in Learning English Vocabulary: University Students’ Perspective - Jessica Ruth Melvira Simanungkalit; Caroline Victorine Katemba (Eduvelop: Journal of English Education and Development, 2023)
This research determined the university students’ perspective on utilizing TikTok in learning English vocabulary. The purpose of this research is: (1). What are college students' thoughts on learning English vocabulary through TikTok? (2). What are the advantages of the TikTok application? (3). What are the disadvantages of the TikTok application? (4). How does the TikTok application help you to learn English vocabulary? This study is qualitative and descriptive and employed a survey method by giving an online questionnaire on Google Forms to university students. The questionnaire is distributed to students in Bandung, Jakarta, and Lampung universities. The subject of this research is university students who are taking English classes. Of the 76 respondents who filled out the questionnaire, 50% were from a private university and 50% were also from a state university. The findings of this research show that utilizing TikTok in learning English vocabulary for university students helps them expand their English vocabulary. The students show positive feedback about utilizing TikTok in learning English vocabulary.